Biochemical Alterations in Inflammation, Oxidative Stress, and Urinary Biomarkers Associated With Renal Damage in Systemic Lupus Erythematosus: Biochemical Markers in SLE Renal Damage - Zhang, Rui; Yu, Yiyang; Liu, Guangxu; Luan, Zhongqiu (Journal of Medical Biochemistry, 2026)
Background: Renal damage is a major complication of systemic lupus erythematosus (SLE) and is closely linked to biochemical disturbances involving inflammation, oxidative stress, and renal tubular injury. However, the biochemical signatures that differentiate SLE patients with and without renal involvement remain insufficiently characterized. To evaluate the biochemical profiles of inflammatory cytokines, oxidative stress markers, and urinary renal-injury biomarkers in SLE patients with and without renal damage, and to explore their associations with microbial alterations.Methods: Sixty-four SLE patients were classified into a renal damage group (n = 36; positive urine protein) and an SLE-only group (n = 28; negative urine protein). Serum cytokines (TGF-β, IL-4, IL-17, IL-1β) and oxidative stress indicators (SOD, T-AOC, MDA) were quantified using ELISA. Urinary microprotein, microglobulin, and N-acetyl-β-D-glucosaminidase (NAG) were used as biochemical markers of renal injury. Oral and intestinal microbial profiles were analyzed by sequencing, and correlations between biochemical markers and microbial alterations were assessed.Results: SLE patients with renal damage showed significantly elevated urinary microprotein, microglobulin, and NAG (all p < 0.001). Inflammatory cytokines were markedly increased in the renal damage group (TGF-β, IL-4, IL-17, IL-1β; all p < 0.05), whereas oxidative stress capacity was significantly reduced (SOD, T-AOC, MDA; all p < 0.05). Several microbial taxa correlated positively or negatively with key biochemical markers, suggesting potential metabolic-immune interactions contributing to renal injury.Conclusions: Renal damage in SLE is characterized by distinct biochemical abnormalities involving intensified inflammation, impaired antioxidant defenses, and elevated urinary renal-injury biomarkers. These biochemical changes, together with specific microbial shifts, may contribute to the progression of SLE-related renal impairment and hold diagnostic value for early biochemical screening.
Keywords: systemic lupus erythematosus; renal damage; biochemical markers; oxidative stress; inflammatory cytokines; urinary biomarkers